Integrated proteomics and metabolomics analysis revealed the mechanisms underlying the effect of irradiation on the fat quality of Chinese bacon. (1st July 2023) - Zhang, Ju; Wang, Tian; Yang, Chunjie; Wu, Ruixiao; Xi, Linjie; Ding, Wu
Graphical abstract: Highlights: Integrated proteomics and metabolomics of irradiated Chinese bacon were performed. Protein/metabolic composition profiles in irradiated Chinese bacon were explored. Irradiation effects on fat quality were partly explained by proteomics/metabolites. Two lipid metabolism pathways related to fat quality of irradiated bacon were seen. Abstract: Irradiation increases the security and storage period of preserved Chinese bacon; nevertheless, the biological mechanisms underlying the changes in fat quality caused by irradiation are unknown. We investigated the influence of irradiation on Chinese bacon by proteomic and metabolomic. We identified 24 proteins that participated in metabolism and 40 common differential metabolites enriched in 16 signalling pathways. Correlation analysis revealed that irradiation altered 11 pathways shared between the proteome and metabolome, including two lipid metabolism pathways. Acetyl-CoA carboxylase, ACSL, octanoic acid, decanoic acid, palmitic acid, and oleic acid participated in fatty acid biosynthesis. Acyl-CoA thioesterase 1/2/4, enoyl-CoA reductase, acetyl-CoA acyltransferase 1, enoyl-CoA hydratase 2, palmitic acid, and oleic acid participated in unsaturated fatty acid biosynthesis. These findings lay the groundwork for multi-omics research on the effects of irradiation on Chinese bacon quality, assisting in assessing irradiated Chinese bacon quality, and developing effective strategies to standardise quality parameters.